The Relationship of Infectious Diseases History and Mother Factors to Under Red Line Among Toddler - Musafaah, Musafaah; Fajriannor, Muhammad (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: Nutrition under the red line is a state of severe nutritional deficiency caused by low consumption of energy and protein from daily food. Sungai Tiung is the village that has the highest number of children under five with under red line (BGM) from other villages in the working area of Rawat Inap Cempaka Health Center. This study aims to know the relationship of infectious diseases history and mother factors to under red line (BGM) among toddler in Sungai Tiung. This research uses cross-sectional design. The samples are 90 respondents. Sampling used purposive sampling. The independent variables are a history of infectious disease, knowledge, education, and mother care pattern. The dependent variable is under red line (BGM). The instrument in this study used questionaire and Kartu Menuju Sehat (KMS). The result showed that there is a relationship history of infectious diseases with BGM (p-value = 0.03). The results also showed no relationship of knowledge (p-value = 0.12), education (p-value = 0.75) and mother care pattern (p-value = 0.32) with BGM. There is a relationship history of infectious diseases with BGM. So that, there should be efforts to prevent infectious diseases in toddler. Keywords : under red line, toddler, infectious diseases